2010
DOI: 10.1089/bsp.2010.0043
|View full text |Cite
|
Sign up to set email alerts
|

Mass Vaccination for the 2009 H1N1 Pandemic: Approaches, Challenges, and Recommendations

Abstract: The 2009 H1N1 pandemic stimulated a nationwide response that included a mass vaccination effort coordinated at the federal, state, and local levels. This article examines a sampling of state and local efforts during the pandemic in order to better prepare for future public health emergencies involving mass distribution, dispensing, and administration of medical countermeasures. In this analysis, the authors interviewed national, state, and local leaders to gain a better understanding of the accomplishments and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 6 publications
0
63
0
1
Order By: Relevance
“…This public health crisis highlighted the role that pharmacists can play and positioned the profession to continue advancing immunization opportunities that improve public health by reaching patient populations in need or at risk. 15,16 There was consensus that adult vaccination rates would also improve if patients had a pharmacy-based immunization benefit. Furthermore, health plan panelists indicated that physicians often carry a limited number of vaccines and that the provision of vaccinations may be a poor utilization of physician time.…”
Section: Expert Panelmentioning
confidence: 99%
“…This public health crisis highlighted the role that pharmacists can play and positioned the profession to continue advancing immunization opportunities that improve public health by reaching patient populations in need or at risk. 15,16 There was consensus that adult vaccination rates would also improve if patients had a pharmacy-based immunization benefit. Furthermore, health plan panelists indicated that physicians often carry a limited number of vaccines and that the provision of vaccinations may be a poor utilization of physician time.…”
Section: Expert Panelmentioning
confidence: 99%
“…24,25 Working with providers to distribute vaccine required effective communication with providers. 9,10,13,18 This enhanced communication with providers, especially those who cared for high-risk patients, might have also increased the ability to push out vaccine-related communication to providers. 2 The tracking of adverse events associated with this new vaccine was a priority for the federal government and impacted states and providers through enhanced tracking of adverse events associated with the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…10 While health departments attempted to prioritize high-risk groups, reallocation of the vaccine was likely necessary because of (1) the way the vaccine was packaged for delivery (i.e., shipment sizes too large for a given practice's needs), (2) the vaccine formulation recommended or contraindicated for certain groups, and (3) the elevated need in some places but not others. 18 This shortage called for the ability of jurisdictions to move vaccines between provider sites. 28 This policy change was necessary in the context of an emergency.…”
Section: Discussionmentioning
confidence: 99%
“…This information was generally provided by surveillance networks, virology laboratories, and national health institutes. By contrast, for pandemics, modelling had a greater impact [73][74][75]. Furthermore, new factors influenced the decision because of the limited data regarding the clinical and epidemiological aspects of pandemics and the ethical and logistical challenges, including public acceptability [33].…”
Section: Vaccine Fundingmentioning
confidence: 99%